Determinants in the adoption of total quality management (tqm) in the construction sector: a management perspective. - García-Bernal, Javier; García-Casarejos, Nieves (Revista de la Construcción. Journal of Construction, 2016)
Although the empirical evidence shows the existence of a positive relationship between the adoption of TQM and an improvement in corporate performance, its dissemination is heterogeneous among companies in the construction sector. The main objective of this paper focuses on identifying the relevant factors that drive executives of construction companies to adopt TQM. Specifically, it analyzes the extent to which company managers’ expectations of the impact of TQM on their business performance determine whether they will adopt TQM or not. The results show that expectations concerning financial improvement, environmental issues, and the satisfaction of customers and employees drive company managers in the construction sector to adopt TQM.